2016
DOI: 10.1016/j.bjid.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of hospital acquired Stenotrophomonas maltophilia isolate biofilms

Abstract: Antibiotics could act synergistically to combat the protection conferred to clinical isolates of Stenotrophomonas maltophilia by biofilms. Macrolide antibiotics may be effective where used in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
4
19
1
2
Order By: Relevance
“…Recently, a systematic review reported that fluoroquinolones show comparable effects on the mortality of S. maltophilia infection compared with trimethoprim-sulfamethoxazole, supporting the use of fluoroquinolones in clinical S. maltophilia infections [39], although high rates of resistance are also increasingly being reported. In the current study, the newer fluoroquinolone levofloxacin showed better activity against S. maltophilia than ciprofloxacin (susceptibility rates: 77.9% versus 18.8%, respectively), confirming previous studies [9,37,38].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, a systematic review reported that fluoroquinolones show comparable effects on the mortality of S. maltophilia infection compared with trimethoprim-sulfamethoxazole, supporting the use of fluoroquinolones in clinical S. maltophilia infections [39], although high rates of resistance are also increasingly being reported. In the current study, the newer fluoroquinolone levofloxacin showed better activity against S. maltophilia than ciprofloxacin (susceptibility rates: 77.9% versus 18.8%, respectively), confirming previous studies [9,37,38].…”
Section: Discussionsupporting
confidence: 89%
“…SXT is the antibiotic of choice for treating S. maltophilia infections, although in recent years, increasing rates of resistance, ranging from 16% to 45%, were reported, especially in CF patients [9,35,36]. Considering available clinical breakpoints, our results confirmed SXT is the most active compound against all the strains tested.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Trimethoprim-sulfamethoxazole (STX) is the first-line antimicrobial combination for the treatment of S. maltophilia infections. However, the allergenic reaction, the intolerance, and the increasing rates of resistance limit the use of Trimethoprim-sulfamethoxazole [18,19]. S. maltophilia infections are also difficult to treat due to the ability of this bacterium to form highly structured and multilayered biofilms [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Non-fermenting Gram-negative bacilli (NF-GNB) colonization and infection are frequent among critically ill patients. Antibiotic resistance is common in NF-GNB, resulting in inappropriate initial antibiotic treatment and poor outcomes 1,11,12,13 . Several outbreaks of infection have been described including a few reports of infections originating outside the hospital setting 14,15,16,17,18 .…”
Section: Discussionmentioning
confidence: 99%